Does Robot Clothing Really Help? User Preferences and Effects in Simulated Domestic Scenarios - Yoshiwara, Kazunari; Kobayashi, Kazuki (Journal of advanced computational intelligence and intelligent informatics, 2025)
This study investigated the impact of clothing on robot appearance, particularly in scenarios where a single robot performs multiple tasks. Clothing depicts an individual’s role and capability toward others. Applying this effect to robot appearance design can enable an individual robot to express roles and capabilities suitable for multiple tasks. This makes it a potentially effective approach to robot appearance design. Our experiments first investigated the user acceptance of robots wearing clothing. Subsequently, we investigated the impact of robot attire on user behavior and impressions in a shared workspace. Our results indicate that users prefer robots to wear clothing only during cooking. In addition, in scenarios wherein robots and users share a workspace while performing different tasks, robot clothing is associated with negative user impressions. These observations indicate that even when users express a preference for clothed robots, the actual effect may not be positive and can vary depending on the task and context of use. Therefore, the decision to clothe a robot requires cautious consideration.